The Belt and Road Initiative. Demographic trends, labour markets and welfare systems of member countries - Michele Bruni (Global Labor Organization (GLO), 2019)
A brief analysis of the different demographic tendencies that will affect the 65 countries of the Belt and Road Initiative allows to point out that they are largely spread along the path of the demographic transition so that in some working age population will dramatically decline, in others will dramatically increase. The implication is that the first group of countries (epitomized by China, Russia, Thailand, but also by Singapore) will be affected by a structural shortage of labour, the second (well represented by India, but also by Pakistan, Egypt and Philippines) by a structural excess of labour. Therefore, for the countries of the first group immigration will not be an option but a necessity, while for the countries of the second group emigration will not be an option but a necessity. The situation suggests that it would be in the interest of all BRI countries to design, develop and implement a policy framework that would allow them to jointly manage migration flows in the amount and with the educational stricture coherent with their needs. However, such a process is extremely difficult and complex and to succeed needs to be properly directed and orchestrated. The paper argues that given its size, the dimension of its need of foreign labour, and its role in the Belt and Road Initiative it is China that should take the lead of a rational approach that falls well inside the strategies of the Initiative.
Keywords: J11; J2; J61; 330; Belt and Road Initiative; China; migration; labour market; demographic transition; demographic polarization